Sustainability of buildings in historic city of Malacca / Wan Hashimah Wan Ismail - Wan Ismail, Wan Hashimah (Faculty of Architecture, Planning and Surveying, 2012)
The paper discusses the sustainability of the buildings on the western side of the Historic City of Malacca with the help of the implementation of conservation policies. It covers the historical background, the role of the local government and the responses of the local residents. The methodology includes site observation, building study, literature review and interview. The findings of the research suggest that the buildings within the area are well sustained but some local residents gave negative responses. Some strategies are needed to ensure the continuous use and sustainability of the buildings.